2013
DOI: 10.1038/onc.2013.230
|View full text |Cite
|
Sign up to set email alerts
|

MiR-221 promotes the development of androgen independence in prostate cancer cells via downregulation of HECTD2 and RAB1A

Abstract: Hormone-sensitive prostate cancer typically progresses to castration resistant prostate cancer (CRPC) after the androgen deprivation therapy. We investigated the impact of microRNAs (miRs) in the transition of prostate cancer to CRPC. MiR-221/-222 was highly expressed in bone metastatic CRPC tumor specimens. We previously demonstrated that transient overexpression of miR-221/-222 in LNCaP promoted the development of the CRPC phenotype. In current study, we show that stably overexpressing miR-221 confers androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 49 publications
5
107
0
Order By: Relevance
“…Yang et al suggested that SIRT1 plays a suppressive role against the tumor promoting action of miR-221 and miR-222 (37). In addition, ADAM17, ARHI and HECTD2 were identified as the target genes of miR-221 and miR-222 (22,38,39). These findings suggest that miR-221 and miR-222 are a therapeutic target.…”
Section: Discussionmentioning
confidence: 97%
“…Yang et al suggested that SIRT1 plays a suppressive role against the tumor promoting action of miR-221 and miR-222 (37). In addition, ADAM17, ARHI and HECTD2 were identified as the target genes of miR-221 and miR-222 (22,38,39). These findings suggest that miR-221 and miR-222 are a therapeutic target.…”
Section: Discussionmentioning
confidence: 97%
“…Aberrant expression of miRs has been well described in human GC (Pan et al, 2013). Specifically, miR-221 has been confirmed to be upregulated and may act as an oncogene in many types of human malignancies (Gimenes-Teixeira et al, 2013;Sarkar et al, 2013;Ergun et al, 2014;Sun et al, 2014;Ye et al, 2014a). Liu et al (2012) reported that upregulation of miR-221 in GC correlated with aggressive clinicopathological features and shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs (miR-21, miR-31, miR-34 and miR-124) can regulate the androgen receptor expression, and simultaneously, AR can regulate the expression of several miRNAs (miR-21, miR-27a, miR-34, miR-125b, miR-221 and let-7) [65]. Goto et al [66] recently demonstrated that miR-221 and 222 were significantly downregulated in CRPC specimens, even when this cluster was previously described to be upregulated ( Figure 3) [67,68]. This fact shows the dynamic status of miRNAs in the development of PCa, regulating the same miRNA different targets depending on the point of the cancer progression.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 92%